RESOLVING THE PROBLEMATIC ARRANGEMENT OF THE TRIUMVIRATE AS INTERIM PRESIDENT IN INDONESIA: INSIGHTS FROM GABON AND AUSTRIA - Auliyaa Rizqan, Rafi; Yusdiyanto, Yusdiyanto; Ridlwan, Zulkarnain (Universitas Lampung, 2024)
This article presents the challenges associated with the triumvirate concept as an interim presidential arrangement in Indonesia and alternative statutory regulations. This normative legal research was performed to determine whether Indonesia's current triumvirate arrangement adequately addresses extraordinary events such as a vacuum of power. The statute approach and the comparative approach were employed in this research. The results showed that Indonesia's triumvirate arrangements are insufficient and comparatively simplistic when contrasted with other countries employing similar concepts. To strengthen Indonesia's framework, it is crucial to examine the regulatory frameworks of comparable nations, with a particular focus on insights from Gabon and Austria.